2021
DOI: 10.1016/j.ijid.2021.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to the inactivated SARS-CoV-2 vaccine among healthcare workers, Indonesia

Abstract: Background As healthcare workers (HCWs) are at high risk for SARS-CoV-2 infection, they have prioritized the COVID-19 vaccine. Inactivated SARS-CoV-2 vaccine has been mainly used in Indonesia to induce HCWs antibody response against SARS-CoV-2 infection. However, information regarding the kinetics of antibody-induced by this vaccine remains scarce. Objective To investigate the magnitude and durability of antibodies against spike (S) protein (anti-S) after complete dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…The antibody level, in particular antibody towards RBD of the S protein (anti-S), has been shown to correlate with virus-neutralizing titres, suggesting the quantification of this antibody can be predictive for SARS-CoV-2 protection (Salazar et al, 2020). Similar to other studies (Kwok et al, 2021;Mok et al, 2021), our study has shown that the decline of anti-S antibodies occurred shortly among the fully vaccinated HCWs with CoronaVac (Cucunawangsih et al, 2021). Considering the short-term immune response after CoronaVac vaccination and the occupational risk of HCWs for acquiring SARS-CoV-2 infection, HCWs are prioritized to receive a booster dose of the mRNA-1273 vaccine.…”
Section: Main Textsupporting
confidence: 84%
“…The antibody level, in particular antibody towards RBD of the S protein (anti-S), has been shown to correlate with virus-neutralizing titres, suggesting the quantification of this antibody can be predictive for SARS-CoV-2 protection (Salazar et al, 2020). Similar to other studies (Kwok et al, 2021;Mok et al, 2021), our study has shown that the decline of anti-S antibodies occurred shortly among the fully vaccinated HCWs with CoronaVac (Cucunawangsih et al, 2021). Considering the short-term immune response after CoronaVac vaccination and the occupational risk of HCWs for acquiring SARS-CoV-2 infection, HCWs are prioritized to receive a booster dose of the mRNA-1273 vaccine.…”
Section: Main Textsupporting
confidence: 84%
“…In this study, the median anti-SARS-CoV-2 IgG antibody level was 335.5 AU/ml (IQR 213.7–499.7) an average of 82 days after a second dose of CoronaVac, which is similar to a study of anti-spike antibodies, which drop significantly by day 42 post immunization in Indonesian HCWs compared to day 14 post CoronaVac vaccination. [26] Vaccine effectiveness against COVID-19 infections also reduced after three to five months in Malaysian subjects who received full CoronaVac vaccination [6] . This seems to indicate that antibody levels following full CoronaVac vaccination drop significantly with time.…”
Section: Discussionmentioning
confidence: 99%
“…The current pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is partially controlled by the availability of COVID-19 vaccines. CoronaVac, an inactivated SARS-CoV-2 and aluminum hydroxide-adjuvanted vaccine (Sinovac Life Sciences, Beijing, China), was the first vaccine used in the COVID-19 emergency vaccination program in Indonesia [ 1 2 ]. The first group in Indonesia to be vaccinated was the healthcare workers (HCWs) as they have a higher risk of SARS-CoV-2 infection compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…We recently had reported our findings on the magnitude and durability of the humoral immunity upon CoronaVac-vaccination among HCWs at various hospitals in Indonesia [ 2 ], demonstrating that two doses of CoronaVac generated seroconversion in most subjects (approximately 99%), based on the detection of anti-SARS-CoV-2 receptor-binding domain (RBD) antibodies. The titer was assessed because as an important subset of SARS-CoV-2-specific neutralizing antibodies, anti-SARS-CoV-2 RBD antibodies inhibit the interaction between the viral RBD and angiotensin-converting enzyme 2 on host cells, thus blocking the viral entry [ 3 ].…”
Section: Introductionmentioning
confidence: 99%